Drawings from the Bequest of W.F. Watson : 1881-1981. - National Gallery of Scotland, Edinburgh (Edinburgh : National Gallery of Scotland, 1981)
Allan, David ; Barocci, Federico ; Biscaino, Bartolomeo ; Blake, William ; Bonington, Richard Parks ; Bol, Hans ; Clerk of Eldin, John ; De Clerk, Hendrick ; etc.
Drawings from the Bequest of WF Watson : 1881-1981, National Gallery of Scotland, Edinburgh, 1981
boek